DEVELOPMENT AND APPLICATION OF POTENTIOMETRIC STRIPPING ANALYSIS - Babincev, Ljiljana M; Gurešić, Dejan M; Simonović, Ranko M (Bulletin of Natural Sciences Research, 2017)
This paper focuses on the voltammetric determination of lead, cadmium and zinc in water. Two ways of determining were investigated: individually and all three metals simultaneously. The experiments were performed using the Potentiometric Stripping Analysis (PSA). Determination of metals in real samples was preceded by preliminary tests. Preliminary investigations were performed in order to determine the optimal conditions of measurement. It was concluded that the process of determining was for most part influenced by: pH, time of metals extraction, stirring rate of the solution and the thickness of the mercury layer on the working electrode. The smallest concentrations of metals which can be determined using this method are: for lead 22.48 μg dm-3, for cadmium 16.23 μg dm-3 and for zinc 18.75 μg dm-3. The obtained results deviated from the actual 1.12% for lead, 1.91% for cadmium and 1.81% for zinc. All tests (individually and simultaneously) were conducted from model solution with concentration as follows: 44.96 μg dm-3 for lead, 32.47 μg dm-3 for cadmium and 37.50 μg dm-3 for zinc. The results of individual measurements deviated by 1.02% lead, 1.90% for cadmium and 1.89% for zinc. Simultaneously the contents were lower than real for: −4.58% for lead, cadmium for −1.91% and −1.89% for zinc. For the conditions determined, except for lead, deviations did not exceed ±2%. This indicates that Potentiometric Stripping Analysis is a good way of individual and simultaneous determination of lead, cadmium and zinc and for determination of their concentrations in water (river and groundwater).